Respuesta :
For this case we have the following expression:
[tex]\frac {b ^ 7} {b ^ 6}[/tex]
By definition of division of powers of the same base, we have to place the same base and subtract the exponents, that is:
[tex]\frac {a ^ m} {a ^ n} = a ^ {n-m}[/tex]
So:
[tex]\frac {b ^ 7} {b ^ 6} = b ^ {7-6} = b ^ 1 = b[/tex]
Answer:
b
Answer: [tex]b[/tex]
Step-by-step explanation:
You need to remember a property called "Quotient of powers property". This property states the following:
[tex]\frac{a^m}{a^n}=a^{(m-n)}[/tex]
You can observe that the bases of the expression [tex]\frac{b^7}{b^6}[/tex] are equal, then you can apply the property mentioned before.
Therefore, you can make the division indicated in the exercise.
Then you get this result:
[tex]\frac{b^7}{b^6}=b^{(7-6)}=b[/tex]